Genetic determinants of heat resistance in Escherichia coli - Mercer, Ryan; Zheng, Jinshui; Garcia-Hernandez, Rigoberto; Ruan, Lifang; Gänzle, Michael; McMullen, Lynn (Frontiers in Microbiology, 2015)
Escherichia coli AW1.7 is a heat resistant food isolate and the occurrence of pathogenic strains with comparable heat resistance may pose a risk to food safety. To identify the genetic determinants of heat resistance, 29 strains of E. coli that differed in their of heat resistance were analyzed by comparative genomics. Strains were classified as highly heat resistant strains, exhibiting a D60-value of more than 6 min; moderately heat resistant strains, exhibiting a D60-value of more than 1 min; or as heat sensitive. A ~14 kb genomic island containing 16 predicted open reading frames encoding putative heat shock proteins and proteases was identified only in highly heat resistant strains. The genomic island was termed the locus of heat resistance (LHR). This putative operon is flanked by mobile elements and possesses >99% sequence identity to genomic islands contributing to heat resistance in Cronobacter sakazakii and Klebsiella pneumoniae. An additional 41 LHR sequences with >87% sequence identity were identified in 11 different species of β- and γ-proteobacteria. Cloning of the full length LHR conferred high heat resistance to the heat sensitive E. coli AW1.7ΔpHR1 and DH5α. The presence of the LHR correlates perfectly to heat resistance in several species of Enterobacteriaceae and occurs at a frequency of 2% of all E. coli genomes, including pathogenic strains. This study suggests the LHR has been laterally exchanged among the β- and γ-proteobacteria and is a reliable indicator of high heat resistance in E. coli.